1989
DOI: 10.3181/00379727-192-42963
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Activated Potassium Channels in Human Platelets

Abstract: The cationic fluorescent probe, DiSC,(5) was used to measure the membrane potential in human platelets. Hyperpolarization was induced by the addition of Ca2+ to the medium and also by the addition of the Ca2+ ionophore, A23187. In the absence of extracellular Ca2+ ([Ca'+],) there was no response to A23187. The threshold concentration for [Ca2+]., was 20 fiM and for A23187 was 12 nM. The increase polarity induced by [Ca2+lO was not affected by various K' channel blockers. However, the effect of A23187 was inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…2), suggesting the presence of Kch channels (which may be IKca channels) in human platelets. This is in agreement with a number of earlier studies on Kca channels in human platelets [5,6,91, which have demonstrated the presence of charybdotoxin-sensitive K+ channels. Furthermore, apamin (100 nmol/l) and charybdotoxin (300nmol/l) added together had a greater effect on thrombin-stimulated 8GRb+ efflux than either alone (Fig.…”
Section: Calcium-activated K+ Channels (B Channels)supporting
confidence: 92%
See 1 more Smart Citation
“…2), suggesting the presence of Kch channels (which may be IKca channels) in human platelets. This is in agreement with a number of earlier studies on Kca channels in human platelets [5,6,91, which have demonstrated the presence of charybdotoxin-sensitive K+ channels. Furthermore, apamin (100 nmol/l) and charybdotoxin (300nmol/l) added together had a greater effect on thrombin-stimulated 8GRb+ efflux than either alone (Fig.…”
Section: Calcium-activated K+ Channels (B Channels)supporting
confidence: 92%
“…2), suggesting the presence of apamin-sensitive SKc, channels in human platelets. In an earlier study, Fine et al [5] measured changes in platelet membrane potential stimulated by the Ca2+ ionophore A23187 in the presence of various Kca channel inhibitors, but found no evidence for the presence of apamin-sensitive K+ channels in human platelets. However, in their experiments apamin was used in a concentration of 25 nmol/l, and the toxin was incubated with the cells for only 2min.…”
Section: Calcium-activated K+ Channels (B Channels)mentioning
confidence: 97%
“…A number of studies have demonstrated the presence of both voltage-operated K ϩ channels and Ca 2ϩ -induced K ϩ channels in the plasma membrane of platelets. [27][28][29][30] The latter can be subdivided in 3 different types, SK (small conductance), IK (intermediate conductance) and BK (large conductance) channels. [31][32][33] Whether or not all 3 types are present in platelets is presently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The rising intracellular Ca++, in concert with activation of the calmodulin system, produces accelerated K+ efflux and enhanced Na+ influx. Indeed, Ca++ activated K + channels have been described in several cell types (Gardos, 1958;Putney et al, 1978;Kurtzer and Roberts, 1982;Martin and Gordon, 1983;Hoffman et al, 1984;Fine et al, 1989). Although we did not have a direct measure of Cai+ activated K + channels, it is possible that the activation of this transport system is ultimately responsible for the enhanced K+ efflux following FBS removal.…”
Section: Discussionmentioning
confidence: 99%